Penilaian Tingkat Kematangan Proses Pengembangan Perangkat Lunak Menggunakan Framework CMMI-Dev 1.3 Pada PT. ABC - Ika Kurniawati; Mochamad Chandra Saputra; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Development process of a software in organization that is in the Information Technology industry will be a determining the success of these organization. PT. ABC is an Information Technology organization that is famous among government. Some of the products that produced by PT. ABC is used in educational world. The best processes of project management are needed for supporting the progress in educational world. Project at PT.ABC had some problems in its implementation. The purpose of this research is to assess the software development maturity level in the Product Development Division of PT. ABC started from the basic project management process using the CMMI for Development 1.3 framework. The result of this research is an actual maturity level of PT. ABC. This research will give improvement recommendations to achieve a higher maturity level based on the CMMI for Development 1.3 framework. The data used in this research were collected using questionnaires and document tracking. The process of appraisal using Standard CMMI Appraisal Method for Process Improvement (SCAMPI) class C. The process areas evaluated in this research are 6 process area which is at maturity level 2. Based on the assessment, from 6 process areas evaluated, there has been no area process that are comply CMMI criteria. From overall of the result, PT. ABC is still at maturity level 1 or initial. Recommendations provided by researchers are expected to help PT. ABC to making improvements according to the CMMI for Development 1.3 framework.